Revised EU approaches to development cooperation. Case study: Triangular cooperation in Bangladesh - Elena-Adina Voicilă (CES Working Papers, 2018)
As the paper assesses, first of all, the role of the European Union (EU) in the development cooperation (ODA) agenda, oriented specifically towards the South Asia region, the analysis will try to identify the opportunities for improving the policy, on one hand, and indicate areas for cooperation between actors involved directly in pursuing poverty eradication and promoting core human values. The main area for cooperation between donors in this case is good governance, due to the chronic problems that the recipient state, Bangladesh, encounters in matters of governance, corruption and rule of law. Therefore, by pinpointing the main theoretical concepts – South-South Cooperation (SSC) and Triangular Cooperation (TrC) – and continuing with a brief policy analysis of the EU ODA in relation with South Asia and Bangladesh and including the Japanese ODA and TrC experience in South Asia, the paper will try to offer arguments in favour of EU to pursue other types of cooperation in the field of development aid
Keywords: 330; Bangladesh; EU; Good Governance; JICA; ODA; Triangular Cooperation